Policy Implications of International Graduate Students and Postdoctoral Scholars in the United States - National Research Council (The National Academies Press, 2005)
Policy Implications of International Graduate Students and Postdoctoral Scholars in the United States explores the role and impact of students and scholars on US educational institutions and the US economy. The nation has drawn increasingly on human resources abroad for its science and engineering workforce. However, competition for talent has grown as other countries have expanded their research infrastructure and created more opportunities for international students. The report discusses trends in international student enrollments, stay rates, and examines the impact of visa policies on international mobility of the highly skilled.
Keywords: Education; Policy for Science and Technology

Immigration Policy and the Search for Skilled Workers: Summary of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
The market for high-skilled workers is becoming increasingly global, as are the markets for knowledge and ideas. While high-skilled immigrants in the United States represent a much smaller proportion of the workforce than they do in countries such as Australia, Canada, and the United Kingdom, these immigrants have an important role in spurring innovation and economic growth in all countries and filling shortages in the domestic labor supply. This report summarizes the proceedings of a Fall 2014 workshop that focused on how immigration policy can be used to attract and retain foreign talent. Participants compared policies on encouraging migration and retention of skilled workers, attracting qualified foreign students and retaining them post-graduation, and input by states or provinces in immigration policies to add flexibility in countries with regional employment differences, among other topics. They also discussed how immigration policies have changed over time in response to undesired labor market outcomes and whether there was sufficient data to measure those outcomes.
Keywords: Industry and Labor

The Integration of Immigrants into American Society - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
The United States prides itself on being a nation of immigrants, and the country has a long history of successfully absorbing people from across the globe. The integration of immigrants and their children contributes to our economic vitality and our vibrant and ever changing culture. We have offered opportunities to immigrants and their children to better themselves and to be fully incorporated into our society and in exchange immigrants have become Americans - embracing an American identity and citizenship, protecting our country through service in our military, fostering technological innovation, harvesting its crops, and enriching everything from the nation's cuisine to its universities, music, and art. Today, the 41 million immigrants in the United States represent 13.1 percent of the U.S. population. The U.S.-born children of immigrants, the second generation, represent another 37.1 million people, or 12 percent of the population. Thus, together the first and second generations account for one out of four members of the U.S. population. Whether they are successfully integrating is therefore a pressing and important question. Are new immigrants and their children being well integrated into American society, within and across generations? Do current policies and practices facilitate their integration? How is American society being transformed by the millions of immigrants who have arrived in recent decades? To answer these questions, this new report from the National Academies of Sciences, Engineering, and Medicine summarizes what we know about how immigrants and their descendants are integrating into American society in a range of areas such as education, occupations, health, and language.
Keywords: Behavioral and Social Sciences

Budgeting for Immigration Enforcement: A Path to Better Performance - National Research Council (The National Academies Press, 2011)
Immigration enforcement is carried out by a complex legal and administrative system, operating under frequently changing legislative mandates and policy guidance, with authority and funding spread across several agencies in two executive departments and the courts. The U.S. Department of Homeland Security (DHS) is responsible for conducting immigration enforcement both at the border and in the United States; the U.S. Department of Justice (DOJ) is responsible for conducting immigration removal procedures and criminal trials and for prosecuting people charged with immigration-related crimes. DOJ confronts at least five technical challenges to modeling its resource needs for immigration enforcement that are specific to the immigration enforcement system. Despite the inherent limitations, budgeting for immigration enforcement can be improved by changing the method for budgeting. Budgeting for Immigration Enforcement addresses how to improve budgeting for the federal immigration enforcement system, specifically focusing on the parts of that system that are operated and funded by the U.S. Department of Justice (DOJ). The report recommends that DOJ establish policy-level procedures to plan and coordinate policy planning and implementation to improve performance of the immigration enforcement system. The report also recommends that DOJ and DHS accelerate their design of an integrated capacity to track cases and project immigration enforcement activity. Policy makers and others who are interested in how the nation's immigration enforcement system is organized and operates also will find it useful.
Keywords: Behavioral and Social Sciences

Options for Estimating Illegal Entries at the U.S.-Mexico Border - National Research Council (The National Academies Press, 2013)
The U.S. Department of Homeland Security (DHS) is responsible for securing and managing the nation's borders. Over the past decade, DHS has dramatically stepped up its enforcement efforts at the U.S.-Mexico border, increasing the number of U.S. Border patrol (USBP) agents, expanding the deployment of technological assets, and implementing a variety of "consequence programs" intended to deter illegal immigration. During this same period, there has also been a sharp decline in the number of unauthorized migrants apprehended at the border. Trends in total apprehensions do not, however, by themselves speak to the effectiveness of DHS's investments in immigration enforcement. In particular, to evaluate whether heightened enforcement efforts have contributed to reducing the flow of undocumented migrants, it is critical to estimate the number of border-crossing attempts during the same period for which apprehensions data are available. With these issues in mind, DHS charged the National Research Council (NRC) with providing guidance on the use of surveys and other methodologies to estimate the number of unauthorized crossings at the U.S.-Mexico border, preferably by geographic region and on a quarterly basis. Options for Estimating Illegal Entries at the U.S.-Mexico Border focuses on Mexican migrants since Mexican nationals account for the vast majority (around 90 percent) of attempted unauthorized border crossings across the U.S.-Mexico border.
Keywords: Behavioral and Social Sciences; Surveys and Statistics

The Economic and Fiscal Consequences of Immigration - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The Economic and Fiscal Consequences of Immigration finds that the long-term impact of immigration on the wages and employment of native-born workers overall is very small, and that any negative impacts are most likely to be found for prior immigrants or native-born high school dropouts. First-generation immigrants are more costly to governments than are the native-born, but the second generation are among the strongest fiscal and economic contributors in the U.S. This report concludes that immigration has an overall positive impact on long-run economic growth in the U.S. More than 40 million people living in the United States were born in other countries, and almost an equal number have at least one foreign-born parent. Together, the first generation (foreign-born) and second generation (children of the foreign-born) comprise almost one in four Americans. It comes as little surprise, then, that many U.S. residents view immigration as a major policy issue facing the nation. Not only does immigration affect the environment in which everyone lives, learns, and works, but it also interacts with nearly every policy area of concern, from jobs and the economy, education, and health care, to federal, state, and local government budgets. The changing patterns of immigration and the evolving consequences for American society, institutions, and the economy continue to fuel public policy debate that plays out at the national, state, and local levels. The Economic and Fiscal Consequences of Immigration assesses the impact of dynamic immigration processes on economic and fiscal outcomes for the United States, a major destination of world population movements. This report will be a fundamental resource for policy makers and law makers at the federal, state, and local levels but extends to the general public, nongovernmental organizations, the business community, educational institutions, and the research community.
Keywords: Behavioral and Social Sciences